Berapa Besar Biaya Audit? Ditinjau Dari Koneksi Politik Dan Tata Kelola - Hendi Hendi; Yulinar Yulinar (Global Financial Accounting Journal, 2017)
The study examines analyze the impact of political connections and corporate governance to audit fee. The dependent variable in this research is audit fee. The selection of auditors having an important role in a company, the company must examine in choosing an auditor to audit the company financial report. Reliable financial report can be obtained from the high quality of auditors. The data used in this research is taken from secondary data that is the annual report data of companies listed on the Malaysia Stock Exchange in the period of 2009 up to 2013. The total sample used in this research is as many as 2650 observation data. The testing of hypotheses was done using analysis regresion. The data are then analyzed using the statistical package for social sciences (SPSS) and Eview 7. This research using purpose sampling methods and the analysis used multiple regression. The result of study indicates that the company which has political connections not have a significant effect to audit fee. Second, corporate governance not have a significant effect to audit fee. on auditors choice.